What decades of policies aimed at agricultural water pollution can teach us about agricultural climate change mitigation: a US perspective - Secchi, Silvia (Frontiers in Sustainable Food Systems, 2023)
The Inflation Reduction Act has catalyzed resources for climate change mitigation in several sectors of the US economy, including agriculture. As these activities ramp up, a clear delineation of the US approach to agricultural climate mitigation is emerging. Practices and policy frameworks are similar to those used to address water quality concerns from agriculture, which started in the 1970s. In fact, some of the programs being deployed to address climate change are the same. In both cases, policies rely on a voluntary approach and subsidies, and focus on practices not outcomes. The experience of agricultural water quality programs can provide useful insights on the effectiveness of the approach being used in agricultural climate change mitigation. Voluntary practices have generally been ineffective in improving water quality. More comprehensive policies, or at least better targeted ones, and more system-based analytical capacity are needed.